MENINGKATKAN KEMAMPUAN MOTORIK KASAR DENGAN PERMAINAN TRADISIONAL ENGKLEK - Klik Purwanto; Endang Tuti Sumarni; M. Anggrayni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to improve children's gross motor skills. In general, today's children are not doing enough physical activity. The problems that occur include the balance and agility of children in moving that are still passive. As a result, children's motor skills have not developed properly. The design of this research is classroom action research (PTK). This research was conducted in Islamic Kindergarten Bakti 50 Sungai Rumbai, the subjects of this study were group B children with 15 children. Data collection techniques using observation and documentation. The results of the study in cycle 1 meeting 1 to 3, the average value of the final observation was 48.89%, and with 15 children. In cycle 2 meetings 1 to 3, the average value of the final observation was 86.67%. So through playing hopscotch activities, you can improve gross motor skills of children in Islamic Kindergarten Bakti 50 Sungai Rumbai.